2021
DOI: 10.1038/s43247-021-00143-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Gulf Stream preceded rapid warming of the Northwest Atlantic Shelf

Abstract: The Northwest Atlantic Shelf provides ecological and economic benefits along the heavily populated North American coastline and beyond. In 2009-2010, abrupt warming prompted an ecosystem shift with consequences for fisheries, yet the cause of this event is unclear. Here we use satellite altimetry and in situ measurements to show that, in 2008, the Gulf Stream migrated closer to the Tail of the Grand Banks, a shift that has persisted ever since. This change reduced the westward connectivity of the Labrador Curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 51 publications
3
59
0
2
Order By: Relevance
“…Heat flux from the atmosphere can lead to the development of marine heatwaves in the surface waters (Chen et al, 2015;Schlegel et al, 2021), and Gulf Stream warm core rings can intrude onto the shelf in the Mid-Atlantic Bight and Georges Bank regions (Gawarkiewicz et al, 2018). However, the recent, decade-long warming event observed in the Gulf of Maine/ western Scotian Shelf slope water can be attributed primarily to the subsurface advection of slope water comprising a relatively large component of Gulf Stream water and a relatively small component of Labrador Current water (Figure 1b; Jutras et al, 2020;Neto et al 2021;Seidov et al, 2021). These warmer and more saline slope water intrusions enter the deep basins and troughs of the Gulf of Maine and the western Scotian Shelf through various deep-water channels, Number of whale icons → Mean SPUE category 0 → 0.0 ≤ SPUE < 0.5 per 100 km 1 → 0.5 ≤ SPUE < 2.5 per 100 km 2 → 2.5 ≤ SPUE < 5.0 per 100 km 3 → 5.0 ≤ SPUE < 7.5 per 100 km 4 → 7.5 ≤ SPUE < 10.0 per 100 km 5 → 10.0 ≤ SPUE < 12.5 per 100 km 6 → 12.5 ≤ SPUE < 15.0 per 100 km FIGURE 3.…”
Section: Discussionmentioning
confidence: 99%
“…Heat flux from the atmosphere can lead to the development of marine heatwaves in the surface waters (Chen et al, 2015;Schlegel et al, 2021), and Gulf Stream warm core rings can intrude onto the shelf in the Mid-Atlantic Bight and Georges Bank regions (Gawarkiewicz et al, 2018). However, the recent, decade-long warming event observed in the Gulf of Maine/ western Scotian Shelf slope water can be attributed primarily to the subsurface advection of slope water comprising a relatively large component of Gulf Stream water and a relatively small component of Labrador Current water (Figure 1b; Jutras et al, 2020;Neto et al 2021;Seidov et al, 2021). These warmer and more saline slope water intrusions enter the deep basins and troughs of the Gulf of Maine and the western Scotian Shelf through various deep-water channels, Number of whale icons → Mean SPUE category 0 → 0.0 ≤ SPUE < 0.5 per 100 km 1 → 0.5 ≤ SPUE < 2.5 per 100 km 2 → 2.5 ≤ SPUE < 5.0 per 100 km 3 → 5.0 ≤ SPUE < 7.5 per 100 km 4 → 7.5 ≤ SPUE < 10.0 per 100 km 5 → 10.0 ≤ SPUE < 12.5 per 100 km 6 → 12.5 ≤ SPUE < 15.0 per 100 km FIGURE 3.…”
Section: Discussionmentioning
confidence: 99%
“…Variability in the productivity data presented here (Figure 5) may support a persistent yet highly variable cool Virginia Current from the north, an extension of the Labrador Current. The position of the gyre and Gulf Stream have been shown to affect the Labrador Current and its extensions to the south [128]. In addition, the PRISM4 paleogeographic reconstruction [21] suggests closure of the Canadian Arctic Archipelago, effectively shutting off the Atlantic connection to the Arctic through the Labrador Sea and Baffin Bay.…”
Section: Paleoclimate Interpretations From Yorktown Formation Datamentioning
confidence: 99%
“…This is consistent with the 4-6 month timescale found by Peña-Molino and Joyce (2008) for sea-surface temperature anomalies to propagate from 60 to 75 • W in the Slope Sea, and with an examination of the model in section 5, which shows that LSLW anomalies would take 9-12 months to travel from the Newfoundland Shelf to the Gulf Stream separation region. Furthermore, Gonçalves Neto et al (2021) found that the propagation of surface velocity anomalies from the TGB to 67 • W takes about 10 months.…”
Section: Summary and Discussionmentioning
confidence: 99%